Implementation of the BPJS Health Referral Program in Indonesia: Literature Review - Jery Ardhan; Rizma Adlia Syakurah; Haerawati Idris; Yuanita Windusari (GLOBAL HEALTH SCIENCE GROUP, 2025)
BPJS Health's Reverse Referral Program (PRB) is an initiative designed to ensure continuity of care for patients with chronic diseases by coordinating between primary healthcare facilities (FKTP) and partner pharmacies. This article aims to review the available literature on the effectiveness of PRB drugs, the flow of referral services, drug availability, and the role of partner pharmacies in supporting program implementation. The method used was a Systematic Literature Review using the Preferred Reporting Items for Systematic Reviews (PRISMA) flow by collecting articles from the Science Direct, Pubmed and Google Scholar databases published between 2019 and 2024 with the keywords